Self-Efficacy in a 3-Dimensional Virtual Reality Classroom-Initial Teacher Education Students' Experiences - Donna Pendergast; Mia O'Brien; Sarah Prestridge; Beryl Exley (MDPI AG, 2022)
This study explores initial teacher education (ITE) university students' experiences of work-integrated-learning (WiL) placements in a virtual reality environment. The COVID-19 pandemic was the catalyst for this study when schools around the world were inaccessible to ITE students. Undertaking WiL, which is typically a mandated component of ITE programs, became challenging, if not impossible. In this uncertain environment and the broader context of a nation-wide teacher shortage in Australia, the need to pivot and consider alternatives became a high priority. This study reports on a simulated experimental space as an alternative WiL for ITE students in a virtual classroom environment, exploring the impact on the self-efficacy of the participants. The ITE students explored the platform as a teaching space, designing, delivering and participating in lessons. Data about their experiences were collected utilising a multi-methods design comprised of self-efficacy surveys and self-reflections. The findings reveal: (i) an increase in self-efficacy upon completion of the experience, with a small decline post program; and (ii) reported development of technological and pedagogical confidence. These findings contribute to the field as low teacher self-efficacy is identified as one of the inhibitors for the integration of technology in teacher education. This study provides an insight into the transformative potential of enhancing ITE students' self-efficacy in simulated, virtual environments.